2011
DOI: 10.1186/ar3452
|View full text |Cite
|
Sign up to set email alerts
|

CD23+/CD21hi B-cell translocation and ipsilateral lymph node collapse is associated with asymmetric arthritic flare in TNF-Tg mice

Abstract: IntroductionRheumatoid arthritis (RA) is a chronic autoimmune disease with episodic flares in affected joints. However, how arthritic flare occurs only in select joints during a systemic autoimmune disease remains an enigma. To better understand these observations, we developed longitudinal imaging outcomes of synovitis and lymphatic flow in mouse models of RA, and identified that asymmetric knee flare is associated with ipsilateral popliteal lymph node (PLN) collapse and the translocation of CD23+/CD21hi B-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
99
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 50 publications
(112 citation statements)
references
References 30 publications
(64 reference statements)
13
99
0
Order By: Relevance
“…Thus, the PLN cannot be a direct measure of lymphatic egress from the knee. To resolve this we tested the hypothesis that LN collapse during asymmetric knee flare in TNF-Tg mice occurs in series along the ipsilateral axis [35]. Consistently, we found that B cells were located within the LYVE-1 + lymphatic sinuses in both collapsed ILN and PLN ipsilateral to flaring knees, and NIR-ICG imaging demonstrated that a decrease in lymphatic transport to the PLN was accompanied with a decrease in transport from the knee to the ILN.…”
Section: Discovery Of Expanding and Collapsed Lymph Nodes And B-inmentioning
confidence: 82%
“…Thus, the PLN cannot be a direct measure of lymphatic egress from the knee. To resolve this we tested the hypothesis that LN collapse during asymmetric knee flare in TNF-Tg mice occurs in series along the ipsilateral axis [35]. Consistently, we found that B cells were located within the LYVE-1 + lymphatic sinuses in both collapsed ILN and PLN ipsilateral to flaring knees, and NIR-ICG imaging demonstrated that a decrease in lymphatic transport to the PLN was accompanied with a decrease in transport from the knee to the ILN.…”
Section: Discovery Of Expanding and Collapsed Lymph Nodes And B-inmentioning
confidence: 82%
“…This collapse, which occurs at variable time intervals in ~80% of TNF-Tg mice, is associated with B-in translocation from the follicles to LYVE-1 + lymphatic vessels of the paracortical sinuses, a reduction in volume and increase in PLN fluid pressure (6, 8, 16). Thereafter, lymphatic drainage declines significantly due to loss of intrisic lymphatic contractions and passive flow (8, 10, 13, 17). It was also demonstrated that B-cell depletion therapy (BCDT) with anti-CD20 antibodies ameliorated knee flare afferent to collapsed PLN by “clearing” the LN sinuses, and restoring passive lymphatic flow in the absence of lymphatic contractions (8).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this model, we have previously shown that progressive joint inflammation in the TNF transgenic (TNF-tg) mouse model of inflammatory-erosive arthritis is accompanied by an increase in draining lymph node’s size, cellularity and drainage capacity, and that disease flares (as detected by increased synovial volume) and bone erosion at the knees are preceded by a rapid decrease in drainage capacity and substantial structural remodeling of the affected nodes [2–5]. These changes are specifically associated with unique alterations in the resident B cell population within the reactive nodes, resulting in the local differentiation of a follicular B cell-derived subset with a unique CD23+, CD21/35-high, CD1d-high, IgM-high, IgD-high phenotype and increased ability to capture and process antigen immune complexes ( B cell in i nflamed n odes, or Bin cells) [46].…”
Section: Introductionmentioning
confidence: 83%
“…These changes are specifically associated with unique alterations in the resident B cell population within the reactive nodes, resulting in the local differentiation of a follicular B cell-derived subset with a unique CD23+, CD21/35-high, CD1d-high, IgM-high, IgD-high phenotype and increased ability to capture and process antigen immune complexes ( B cell in i nflamed n odes, or Bin cells) [46]. Most significantly from a pathogenic standpoint, Bin cells localize to, and substantially occupy paracortical sinusoids in collapsed TNF-tg lymph nodes, likely contributing to the decreased lymphatic drainage function of the nodes [2–5, 7, 8]. Consistent with this hypothesis, in vivo depletion of B cells in TNF-tg mice using anti-CD20 antibodies restores lymphatic drainage and ameliorates disease progression [4, 8].…”
Section: Introductionmentioning
confidence: 99%